PENGARUH TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PENGETAHUAN PEPAJAKAN SEBAGAI PEMODERASI - Axel Axel, Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Tax is the largest source of state revenue for the Indoensian budget. Efforts by the government to obtain state revenues through taxes are still not effective. Therefore, the government held a socialization on taxes and set tax amnesty policy. This study aims to determine the effect of tax amnesty on individual entrepreneurs taxpayer compliance with knowledge of taxation as a moderating variable. The population of this study is an individual entreprenuers taxpayer who conducts business activities in ITC Cempaka Mas. Data and information obtained from the questionnaires filled out by respondents, 100 individual entrepreneurs taxpayers. This research was conducted by distributing questionnaires with judgmental sampling technique. This research use likert scale; SPSS 22; Test Validity and Reliability; Classic assumption test; Hypothesis testing. The result of data analysis shows that tax amnesty have positive and significant effect to individual entrepreneurs taxpayer compliance. Taxation knowledge has a positive and significant effect on taxpayer compliance of private entrepreneur. Another result that can be concluded is the knowledge of taxation has no effect in moderating the relationship between tax amnesty and individual entrepreneurs taxpayer complianceKeywords : Tax Amnesty, Taxation Knowledge, and Individual Entrepreneurs Taxpayer Compliance